2010
DOI: 10.1902/jop.2010.090732
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Cytokines in Subjects With Generalized Chronic and Aggressive Periodontitis Before and After Non‐Surgical Periodontal Therapy: A Pilot Study

Abstract: Subjects with GAgP presented higher levels of TNF-alpha and IL-17 than subjects with GCP and PH subjects. In addition, although the serum levels of these cytokines improved significantly as a result of periodontal therapy, the levels of TNF-alpha remained higher in subjects with GAgP compared to PH subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
91
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 44 publications
17
91
3
6
Order By: Relevance
“…The earlier investigation involved a greater number of participants with a greater variation in the level of periodontitis, whereas in this study The circulating levels of IL-17A (range 2 pg/ml -360 pg/ml), IL-17E (4 pg/ml -96 pg/ml), TNF (range = 0 pg/ml -42 pg/ml) and IL-6 (range = 0 pg/ml -34 pg/ml) reported in this study are similar to levels reported in other studies [7,8,13,14]. In addition the trends in these mediators post-therapy are generally in agreement with other studies [7,8,13,14]. While there is no exact agreement on the timing of reassessments between studies, some comparisons can be made.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The earlier investigation involved a greater number of participants with a greater variation in the level of periodontitis, whereas in this study The circulating levels of IL-17A (range 2 pg/ml -360 pg/ml), IL-17E (4 pg/ml -96 pg/ml), TNF (range = 0 pg/ml -42 pg/ml) and IL-6 (range = 0 pg/ml -34 pg/ml) reported in this study are similar to levels reported in other studies [7,8,13,14]. In addition the trends in these mediators post-therapy are generally in agreement with other studies [7,8,13,14]. While there is no exact agreement on the timing of reassessments between studies, some comparisons can be made.…”
Section: Discussionsupporting
confidence: 91%
“…While there is no exact agreement on the timing of reassessments between studies, some comparisons can be made. Indeed, at the 6 week post-treatment reassessment (R1) findings for TNF and IL-6 were similar to results reported in other studies [7,[13][14][15][16][17]. However, unlike some other studies, an increase in the levels of IL-6 and TNF, was observed after R1 with higher levels being recorded at R2; although these generally remained below baseline values.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations